2004
DOI: 10.1111/j.1743-6109.04041.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Erectile Dysfunction Among Young Adults: Results of a Large-Scale Survey

Abstract: Introduction Erectile dysfunction (ED) can be an early and first sign of an underlying systemic disease. A screening program is offered by the Medical services of the Israel Defense Force for career servicemen at the Staff Periodic Examination Center (SPEC) aimed at early detection of morbidity. The Sexual Human Inventory for Males (SHIM) questionnaire was introduced to these men in order to identify ED, to offer men with ED suitable treatment options, and to investigate underlying systemic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 27 publications
5
66
0
5
Order By: Relevance
“…In a cross-national, population-based survey in five European countries and the United States, the prevalence of ED among men younger than 40 years ranged from about 2% to 9% 25. Nevertheless, a prevalence of ED >10% may be found among men under 40 years of age, an example for this being provided by a survey conducted in Austria, where a prevalence of 25% was found,26 and one in Israel, with a prevalence of 22% being found among men in the Israel Defence Forces 27. Both of these studies used classifications based on the IIEF.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-national, population-based survey in five European countries and the United States, the prevalence of ED among men younger than 40 years ranged from about 2% to 9% 25. Nevertheless, a prevalence of ED >10% may be found among men under 40 years of age, an example for this being provided by a survey conducted in Austria, where a prevalence of 25% was found,26 and one in Israel, with a prevalence of 22% being found among men in the Israel Defence Forces 27. Both of these studies used classifications based on the IIEF.…”
Section: Discussionmentioning
confidence: 99%
“…Other forms of ED also appear to be prevalent among young men in the Middle East. Heruti et al, 7 conducted a large-scale study that included 5836 young men and reported a 22.1% prevalence of ED in men under the age of 40 years based on low SHIM scores (o21). Clearly Public awareness and sex education programs are needed to help young men and women understand and cope with this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Measures used in this study are described below. The quantification of ED followed the EF domain (six items) of the IIEF, facilitating the differentiation between no ED (score [26][27][28][29][30], mild ED (score [22][23][24][25], mild to moderate ED (score 17-21), moderate ED (score [11][12][13][14][15][16], and severe ED (score 1-10) [31]. ED was defined as an EF score between 1 and 25.…”
Section: Sexual Quality Of Life Ed and Agementioning
confidence: 99%
“…Likely for methodological differences, results from surveys indicate a large variation in the prevalence of ED ranging between 15% and 50% [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In Germany, recent data point to 19-48% men affected [4,19].…”
Section: Introductionmentioning
confidence: 98%